Nonresonant inelastic x-ray scattering involving excitonic excitations: the examples of NiO and CoO - Haverkort, Maurits W. (Physical review letters, 2007)
In a recent publication Larson et al. reported remarkably clear d−d excitations for NiO and CoO with x-ray scattering. Here we present an accurate quantitative description based on a local many body approach, beyond local density approximation + Hubbard U approximations. The magnitude of →q determines which of the allowed multipoles contributes most to the spectra. The direction of →q with respect to the crystal can be used as an equivalent to polarization similar to electron energy loss spectroscopy, allowing for a determination of the local symmetry of the initial and final states. This method is more generally applicable and could be a powerful tool for the study of local distortions and symmetries in transition metal and rare earth compounds.